Post a New Question

pre calculus

posted by .

Write the expression below as a single logarithm. Need to know how to work this!
ln(x-5/x^2 - 1) - ln (x^2 - 2x -15/x + 1)

  • pre calculus -

    ln(x-5/x^2 - 1) - ln (x^2 - 2x -15/x + 1)
    = ln(x-5) - ln(x^2 - 1) - (ln(x-5)(x+3) - ln(x+1) )
    = ln(x-5) -( (ln (x+1) + ln(x-1) ) - ( ln(x-5) + ln(x+3) - ln(x+1) )
    = ln(x-5) - ln(x+1) - ln(x-1) - ln(x-5) - ln(x+3) + ln(x+1)
    = -( ln(x-1) + ln(x+3) )
    = -ln( (x-1)(x+3) )
    or -ln(x^2 + 2x - 3)

  • pre calculus -

    Thank you!

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

More Related Questions

Post a New Question